The Income Analysis and Development Strategy of Durian Farming - Prasto, Georgius Lingga; Prajanti, Sucihatiningsih Dian Wisika (Efficient: Indonesian Journal of Development Economics, 2020)
The purpose of this study was analyzing durian arming, formulated the strategy to develop durian farming, and knowing the problems also the alternative solution to develop durian farming in Jambu district Semarang Regency . The data analysis method in this research uses income analysis and Analytical Hierarchy Process (AHP). The type of data used are primary data and secondary data, primary data obtained from observations, interviews and questionnaires, while secondary data are obtained from the Central Statistics Agency (BPS) and the Department of Agriculture. The results showed that the income of durian farming in Jambu District was still profitable, namely Rp. 25,714,063 with an R / C Ratio of 3.86 which showed that durian farming in Jambu District was profitable. The results of the AHP analysis showed that the first development strategies were aspects of cultivation (51%), marketing (21.3%), production factors (16.4%), post-harvest (6%), and institutional humidity (5.1%). Suggestions: 1) conduct Good Handling Practices (GHP) as a guideline for truly cultivation, harvesting, post-harvest processes so that farmers can increase their farming income; 2) The application of modern agriculture such as the top working method, namely improving the quality of trees by connecting the stems with seedlings; 3) Increasing knowledge supports farming by socializing and attending workshops related to farming cultivation. Tujuan penelitian ini adalah menganalisis pendapatan usahatani durian, memformulasikan strategi pengembangan usahatani durian, dan mengetahui hambatan serta solusi alternative pengembangan usahatani durian di Kecamatan Jambu Kabupaten Semarang. Metode analisis data dalam penelitian ini menggunakan analisis pendapatan dan Analytical Hierarchy Process (AHP). Jenis data yang digunakan adalah data primer dan data sekunder, data primer di dapatkan dari observasi, wawancara dan kuesioner, sedangkan data sekunder didapat dari Badan Pusat Statistik (BPS) dan Dinas Pertanian. Hasil penelitian menunjukkan bahwa pendapatan usahatani durian di Kecamatan Jambu masih menguntungkan yaitu sebesar Rp 25.714.063 dengan R/C Ratio 3.85 yang menunjukan usahatani durian di Kecamatan Jambu menguntungkan. Hasil analisis AHP menunjukan prioritas strategi pengembangan yang pertama adalah aspek budidaya (51%), pemasaran (21.3%), faktor produksi (16.4%), pasca panen (6%), dan kelembagaan (5.1%).Saran: 1) Melakukan Good Handling Practice (GHP) sebagai pedoman proses budidaya, panen, pasca panen yang benar agar petani dapat meningkatkan pendapatan usahataninya; 2) Penerapan pertanian modern seperti metode top working yaitu perbaikan kualitas pohon dengan penyambungan batang dengan bibit unggulan; 3) Peningkatan pengetahuan pelaku usahatani dengan sosialisasi dan mengikuti workshop terkait budidaya usahatani.